Atitudini ale unor instituţii şi autorităţi publice faţă de minorităţi în România – aşa cum rezultă din activitatea instituţiei Avocatul Poporului – - Vasile BURTEA (Polis: Revista de Stiinte Politice, 2017)
The present study aims at highlighting the relations between the legal frame and the institutional frame at a particular historic moment of its development, respectively the period of transition from the centralized economy to the free market economy. The present study is emphasizes the dysfunctional gap between the expectations and the effective achievements within the formal frame of public administration, considered to be the prominent marker related to the civilization level and the social philosophy specific to a certain people, as regards the organizational and the functioning points of view. In respect that the analysis deliberately remains at the stage of empiric research, we reckon that the reader may retain the conclusions in accordance with one sown personality and exigency.